OpenGL Based Real Time&Inline Simulation of CNC Cams Grinding - Hu Zhanqi; Xie Mingli (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
OpenGL based NC machining real time simulation model is proposed in the paper, and some key techniques of the system are investigated, including input and compiling of NC program, building of display model, real time displaying procedure of machining. With this technique, operator can view the machining process at screen of CNC machining real time, without stopping machine tool, which is very convenient for operating of machining. At last of the paper, an example of CNC cams grinding machine tool is given in order to proving the algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2644